Salisbury screen absorbers using epsilon-near-zero substrate. (13th January 2021) - Wulan, Qiqige; He, De; Zhang, Tieyan; Peng, Hao; Liu, Lu; Medvedev, Viacheslav V; Liu, Zhijun
Abstract: As a planar resonant structure, Salisbury screen offers a cost-effective way of manipulating electromagnetic waves for both fundamental studies and practical applications in optoelectronics. In this paper, we demonstrate Salisbury screen absorbers using epsilon-near-zero substrate, which reduces the spacer thickness below typical one quarter wavelength limit. Three-layered thin-film absorbers made of SiC substrate, ZnSe spacer layer and top NiCr film are designed and fabricated, which exhibit near-perfect absorption at 11.72 μ m with spacer thickness of about half of a quarter-wavelength. For ideal zero-index material without optical loss, our proposed thin-film absorber simplifies to a two-layered structure even without the spacer layer in theory. These results suggest that epsilon-near-zero materials provide an alternative approach in developing compact planar absorbing structures without involving lithographic patterning.